Avaliação da temperatura de indução e de fontes de nitrogênio na produção de proteína de superfície de Streptococcus pneumoniae em Escherichia coli recombinante - Santos, Mauricio Possedente dos (2012)
Diseases caused by Streptococcus pneumoniae are one of the main problems of public health in the world. The pneumococcal surface protein A(PspA) is a potential canditate as carrier in a conjugate vaccine against this bacteria. Considering the inherent high losses of the purification and conjugation steps, it is fundamental to adopt a strategy of cultivation and expression that allows the obtainance of large quantities of protein. Thus, the use of Escherichia coli as expression system as well as its cultivation in complex medium constitutes promising alternatives for reducing the cost and increasing the productivity of the process. The goal of this work was to study the influence of the temperature and cultivation medium composition over the production of a PspA belonging to clade 4 protein fragment (PspA4Pro) during rE coli cultivations, aiming at to evaluate the possibility of employing vegetable-based nitrogen sources (soybean protein hydrolisates) instead of the Triptona, an animal-derived nitrogen source. The experiments were carried out in both shakers and benchscale bioreactor, using a complex medium which contained glucose and glycerol as carbon sources, lactose as inducer and Soytone, Phytone or Triptone as nitrogen sources, besides yeast extract. Samples were collected during the experiments to follow the cell growth (measurements of absorbance, dry cell weight and permittivity signal from biomass sensors), the carbon sources consumption and the production of organic acids by HPLC analysis. The stability of the plasmid (agar plates with or without kanamycin) and the production of recombinant protein (Bradford and SDS-PAGE electrophoresis followed by densitometry) were also evaluated. Preliminary experiments were performed in shake flasks, incubated at 300rpm and 37ºC, employing both complex and defined media. The highest productivity was achieved in complex medium, with a 42% superior protein production. Subsequently, nine complementary experiments were conducted in shake flasks with complex medium, under the agitation of 300rpm and temperatures of 37ºC (growth phase) and 25, 31 or 37ºC (induction phase). The largest specific production of soluble PspA4Pro was verified at 25ºC, reaching, respectively, 209±6, 192±5mg/g dry cell mass for Phytone and Triptone, with final absorbance values (after 12h of induction) of 9.0±0.4 and 8.5±0.4. The best protein production for Soytone (124±4mg/g dry cell weight) was observed at 31ºC, yielding a final absorbance 8.0±0.4. From the results obtained in the preliminary tests, the nitrogen source Phytone was selected for experiments in bioreactor. Four batch cultures were conducted in bench-scale bioreactor (5L), containing a modified auto-induction complex medium (10g/L glucose, 60g/L glycerol and 20g/L lactose), being three of them with Phytone and one with Triptone, for comparison. The best results in terms of protein production (245±7mg of PspA4Pro soluble/g dry mass) were obtained in the presence of Phytone, corresponding to an increase of 16% towards the maximum value achieved in the cultivation with Triptone. These results demonstrate the potential of vegetable-based nutrients as alternatives to animal-derived nitrogen sources in complex media, contributing to adequate these media formulations to the current guidelines of good manufacturing practices.